2003
DOI: 10.1097/01.mp.0000056631.15739.1b
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ear and Temporal Bone Meningiomas: A Clinicopathologic Study of 36 Cases with a Review of the Literature

Abstract: "Primary" ear and temporal bone meningiomas are tumors that are frequently misdiagnosed and unrecognized, resulting in inappropriate clinical management. To date, a large clinicopathologic study of meningiomas in this anatomic site has not been reported. Thirty-six cases of ear and temporal bone meningiomas diagnosed between 1970 and 1996 were retrieved from our files. Histologic features were reviewed, immunohistochemical analysis was performed (n ‫؍‬ 19), and patient follow-up was obtained (n ‫؍‬ 35). The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
107
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 56 publications
3
107
0
9
Order By: Relevance
“…Embryologically, ectopic meningiomas are postulated to arise from either ''punched off'' embryonal arachnoid cells outside the skull and vertebra that lie along the line of fusion of the primitive nerve or bone sheaths, or it may arise as a result of differential maturation of pluripotent mesenchymal cells (2,7). The first theory is more widely accepted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Embryologically, ectopic meningiomas are postulated to arise from either ''punched off'' embryonal arachnoid cells outside the skull and vertebra that lie along the line of fusion of the primitive nerve or bone sheaths, or it may arise as a result of differential maturation of pluripotent mesenchymal cells (2,7). The first theory is more widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Only an estimated 2% of meningiomas occur extracranially (1); middle ear or temporal bone involvement of meningioma is extremely rare. Thompson et al (2) reported 36 cases of ear and temporal bone meningiomas diagnosed between 1970 and 1996. Many cases of middle ear meningioma were not isolated middle ear meningiomas, but had primary intracranial lesions with involvement of the middle ear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the location of the tumor, patients can present with a variety of neurological symptoms, including headaches, speech problems, visual disturbances, cognitive deficits, motor deficits and epilepsy (4). In cases of temporal bone meningioma, otalgia is the most common feature, although hearing loss (conductive, mixed or sensorineural) (14), facial palsy and tinnitus are also common (15). A lower proportion of patients present with other cranial nerve palsies or vestibular symptoms (16).…”
Section: Discussionmentioning
confidence: 99%
“…8 An MRI with gadolinium enhancement is superior to plain X-ray or CT scan for differentiating peripheral extension of an intracranial meningioma from the less common primary extracranial meningioma (as encountered in our patient). 3,8 The differential diagnosis of a middle-ear mass includes schwannoma, glomus tumour, metastatic tumour and ceruminous gland tumour. Differentiation of middle-ear meningioma from facial nerve schwannoma is clinically difficult, due to these tumours' similar clinical presentations.…”
Section: Discussionmentioning
confidence: 99%